Adubação fosfatada de longo prazo em vinhedos: nutrição, produção e composição da uva - Silva, Lincon Oliveira Stefanello da (2022)
Viticulture occupies an area of approximately 7.3 million hectares worldwide and 75 thousand hectares in Brazil. The State of Rio Grande do Sul (RS) is responsible for more than 60% of the area cultivated with vines in the country. Among the grape production regions in the state, Campanha Gaúcha is the pioneer in the cultivation of wine vines (Vitis vinifera L.). In this region, vineyards are usually implanted in sandy, acidic soils, with low soil organic matter (SOM) and low natural phosphorus (P) availability. Thus, it is necessary to apply limestone and phosphate fertilizers to make grape production viable. However, as P is a non-renewable resource with finite reserves, its rational use becomes economically and environmentally essential. Thus, long-term field studies, which provide information about the seasonality of the nutritional demand of vines, as well as strategies adopted by these plants to recover this nutrient from the soil, are promising from a sustainable point of view. This can be achieved through the combined use of data from long-term experiments and advanced mathematical tools, such as the Bayesian approach. The objective of this study was to evaluate the effects of long-term phosphate fertilization in vineyards on vine nutrition and production and grape quality. Thus, three Studies were carried out in vineyards with a long history of P application to the so il. The studies performed in southern Brazil, and the white and red vine cultivars were 'Chardonnay' and 'Pinot Noir', respectively. Study I established critical levels of P in the soil of 37 mg dm-3, in leaves sampled at flowering of 1,63 g kg-1, and in leaves sampled at veraison of 1.12 g kg-1 (‘Chardonnay’) and 1.38 g kg-1 (‘Pinot Noir’). It implied maximum technical efficiency doses of 42 and 66 kg P2O5 ha-1, respectively, for these cultivars. Study II showed that ‘Pinot Noir’ grapevines are at least twice more responsive to P supply than ‘Chardonnay’. The number of clusters is the main yield component. Additionally, as yield increases, the berry components decrease. The P concentration in leaves at flowering is a good indicator of total soluble solids in grape berries. Lastly, from Study III, we verified that ‘Pinot Noir’ grapevines can recover four-fold more P under a high P supply. Furthermore, soil inorganic and organic P pools are the most affected in long term. The results obtained from these studies will enable to obtain higher yields in vineyards. Additionally, they will optimize the use of phosphate fertilizers, reducing the potential for environmental contamination and increasing the profitability of winegrowers. Likewise, they will help the winegrower in the vineyard logistics, allowing management practices in the current season to estimate the quality of the grapes at harvest.